The Influence of Return On Asset (ROA), Net Profit Margin (NPM), and Debt to Equity Ratio (DER) Flows to Practice of Income Smoothing (Study at Food and Beverages Companies On List In The Indonesia Stock Exchange Period 2013-2016) - Yolanda Atika Sari; Siti Hayati Efi Friantin; Yuniatin Trisnawati DKW (ADVANCE, 2018)
The study aims to analyze (1) influence of Return On Asset towards practical income smoothing (2) influene of Net Profit Margin towards practical income smoothing (3) influence of Debt to Equity Ratio towards practical income smoothing towards food and beverages company that is listed in the stock exchange of Indonesia as at 2013-2016. Sampel selection is done by using purposive sampling method with predetermined criteria. The result of the research shows that (1) Return On Asset does have a significant negative influence towards the practical income smoothing with regression coefficient value is – 1,447 and the significance value is 0,027. (2) Net Profit Margin also has a significant positive influence towards the practical income smoothing with regression coefficient value is 1,816 and the significance value is 0,014. (3) Debt to Equity Ratio does have a significant negative influence towards the practical income smoothing with regression coefficient value is -0,082 and the significance value is 0,035.Keywords : Return On Asset, Net Profit Margin, Debt to Equity Ratio, Income Smoothing.